2017
DOI: 10.25177/jfst.1.3.4
|View full text |Cite
|
Sign up to set email alerts
|

Alteration in Escherichia coli and Streptococcus faecalis cells induced by ozone

Abstract: ABSTRACT:To elucidate ozone action mechanism, cell suspensions of E. coli 8099 and S. faecalis ATCC29212 were initially exposed to ozone for 5 min, and then treated with sodium dodecyl sulfate, sodium hydroxide, and proteinase K. those of S. faecalis were 7.95±2.81%-55.85±1.43%. After ozone pre-treatment, OD600 value of E. coli cells, sequently treated with SDS, NaOH, and PK, decreased by 8.83±1.86%, 34.72±0.42%, and 10.42±2.08%, respectively. And that of S. feacalis decreased by 2.85±3.63%, 71.30±1.08%, and 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
1
0
0
Order By: Relevance
“…These results are similar to those found by Zhang et al [61] and Giuliani et al [24], who, in their studies on the effect of ozonized water on different types of bacteria, reported that the effect of the ozonation process was greater in the action on Gram-positive microorganisms. However, in this work, a similar effect was observed for P. aeruginosa, which is a Gram-negative bacterium.…”
Section: Biocidal Effect Of Ozonized Tap Watersupporting
confidence: 92%
“…These results are similar to those found by Zhang et al [61] and Giuliani et al [24], who, in their studies on the effect of ozonized water on different types of bacteria, reported that the effect of the ozonation process was greater in the action on Gram-positive microorganisms. However, in this work, a similar effect was observed for P. aeruginosa, which is a Gram-negative bacterium.…”
Section: Biocidal Effect Of Ozonized Tap Watersupporting
confidence: 92%